Evaluasi Kapasitas Saluran Drainase di Catchment Area Sub Sistem Bendul Merisi Kota Surabaya - Danayanti Azmi Dewi Nusantara (U Karst, 2020)
Bendul Merisi is a densely populated urban village located in the city of Surabaya with a population density, which until 2014 reached 12,477 inhabitants. The drainage channel in Bendul Merisi is unable to collect rainwater, causing water overflow in the drainage canal. The way to overcome flood is to increase the capacity of the channel. Evaluation of drainage channel capacity in Bendul Merisi is needed for flood management. The purpose of this study is to find out the amount of capacity of the drainage channel, so flood can be overcome, can find out the results of the evaluation of flood volume for the next 2 years with the existing channel capacity. The results of this study are the dimensions of the tertiary channel 2 using a width of 1.9 m and a depth of 2.1 m; quarterly channel 1 uses a width of 0.6 m and a depth of 1.5 m; Q2 channel uses a width of 2 m and a depth of 2.98 m. The expansion of the cross-section is expected to be overcome.Bendul Merisi merupakan kelurahan padat penduduk yang terletak di Kota Surabaya dengan kepadatan penduduk yang sampai pada tahun 2014 mencapai 12.477 jiwa. Saluran pembuang di Bendul Merisi tidak mampu menampung air hujan  sehingga mengakibatkan meluapnya air di saluran pembuang banjir. Cara penanggulangan banjir adalah memperbesar kapasitas saluran. Evaluasi kapasitas saluran drainase di Bendul Merisi diperlukan, untuk penanganan banjir. Tujuan dari penelitian ini dapat mengetahui jumlah kapasitas tampungan saluran drainase, sehingga bajir dapat teratasi, dapat mengetahui hasil evaluasi volume banjir untuk 2 tahun yang mendatang dengan kapasitas saluran yang ada. Hasil penelitian ini adalah dimensi saluran tersier 2 menggunakan lebar 1,9 m dan kedalaman 2,1 m; saluran kuarter 1 menggunakan lebar 0,6 m dan kedalaman 1,5 m; saluran kuarter 2 menggunakan lebar 2 m dan kedalaman 2,98 m. Pembesaran penampang diharapkan banjir dapat teratasi.